Choriocapillaris Vascular Density Changes in Patients with Drusen: Cross-Sectional Study Based on Optical Coherence Tomography Angiography Findings - Chatziralli, Irini (Ophthalmol Ther, 2018)
INTRODUCTION: The purpose of this study was to investigate the extent and morphology of the choriocapillaris’ density defect in patients with drusen in non-neovascular age-related macular degeneration (AMD). METHODS: Participants in this study were 36 patients with non-neovascular AMD and drusen. All patients underwent best-corrected visual acuity, slit-lamp examination, spectral domain-optical coherence tomography (SD-OCT), and optical coherence tomography angiography (OCTA). RESULTS: In all studied cases, the presence of drusen was associated with choriocapillaris’ reduced blood flow signal of different extent and severity. Three types of choriocapillaris’ non-perfusion were observed, along with an association between the size of drusen and the morphology of choriocapillaris’ density defect. Moreover, the extent of choriocapillaris’ density change has been related to ellipsoid zone disruption and therefore to visual impairment. CONCLUSIONS: Our study showed that in patients with drusen due to non-neovascular AMD, there is choriocapillaris’ impairment of different morphology in OCTA, which is mainly related to the size and location of the drusen.